Intratympanic Gentamicin for Intractable Ménière's Disease – A Review and Analysis of Audiovestibular Impact - Yetişer, Sertaç (International Archives of Otorhinolaryngology, 2018)
Introduction Intratympanic gentamicin regulates the symptoms in most patients with incapacitating Ménière's disease. The treatment protocols have changed over the years from medical labyrinthectomy to preservation of vestibular function.Objectives This study aims to review the audiovestibular response related to the effect of the drug in controlling vertigo.Data Synthesis Articles were identified by means of a search in the PubMed database using the key words Meniere and intratympanic or transtympanic gentamicin. Total 144 articles were reviewed after excluding those that were technical reports, those based on experimental animal studies, those that focused on outcomes other than vertigo (tinnitus or aural fullness), those with delivery methods other than tympanic membrane injection, and those with bilateral cases. If there was more than one article by the same author(s) or institution, only the most recent one matching the aforementioned criteria and those that were not overlapping were included.Conclusion Titration methods or multiple injections on a daily basis can be preferred if the patients have profound or non-serviceable hearing, since these methods have significant incidence of hearing loss. Treatment protocols with a frequency of injection not shorter than once a week, or those with injections on a monthly basis as “needed” provide the same level of vertigo control with better preservation of hearing. Caloric testing is not an ideal tool to analyze the correlation between vertigo control and the effect of gentamicin as compared with gain asymmetry of the vestibulo-ocular reflex. Vestibular-evoked myogenic potentials and the head thrust test are more reliable than other vestibular tests for the follow-up of patients undergoing gentamicin treatment.
Keywords: Ménière's disease; intratympanic gentamicin; vertigo